The effect of age, sex, and resource abundance on patterns of rake markings in resident killer whales (Orcinus orca). Issue 3 (24th January 2022) - Grimes, Charli; Brent, Lauren J. N.; Weiss, Michael N.; Franks, Daniel W.; Balcomb, Kenneth C.; Ellifrit, David K.; Ellis, Samuel; Croft, Darren P.
Abstract: Fluctuations in aggressive behavior of group‐living species can reflect social conflict and competition for resources faced by individuals throughout their lifespan and can negatively impact survival and reproduction. In marine mammals, where social interactions are difficult to observe, tooth rake marks can be used as an indicator of received aggression. Using 38 years of photographic data, we quantified the occurrence of tooth rake marks on wild resident killer whales ( Orcinus orca ), examining the effects of age, sex, and prey abundance on rake density. Our analysis revealed sex and age effects, with males exhibiting higher rake density than females and rake density declining significantly with age. Contrary to predictions, we observed an increase in rake density across the population as the abundance of their primary food resource, Chinook salmon ( Oncorhynchus tshawytscha ), increased. These results provide indirect evidence of fluctuations in received aggression from conspecifics across the lifespan of an individual, possibly reflecting changes in patterns of social conflict which may be mediated by resource abundance. Our findings highlight the need for further research to examine the fitness consequences of aggression in killer whales and to understand the proximate mechanisms by which resource abundance influences rates of aggression in the population.